Influence of hypertension diagnosis and subjective life expectancy on health behaviors among middle-aged and older Chinese adults - Xiaoxiao Liu; Xiaoyi Ji; Honghong Xia; Yuxin Tian; Weihong Zheng; Linyun Fu; Peiyuan Qiu; Yang Wan (Frontiers in Public Health)
ObjectivesHypertension can lead to significant health complications if left unmanaged due to unhealthy behaviors. This study investigates hypertension related health behaviors of middle-aged and older Chinese adults, investigating whether a hypertension diagnosis and individuals’ subjective life expectancy (SLE) might prompt positive changes in their health behaviors.MethodsThe participants in this study were Chinese adults aged 45 years and older, selected from the 2013–2020 China Health and Retirement Longitudinal Study. Linear mixed-effects models were employed to investigate the influence of receiving a hypertension diagnosis, as well as SLE, on hypertension related behaviors.ResultsAmong the respondents, 27.65% reported doctor-diagnosed hypertension, while 19.91% of those who were undiagnosed with hypertension had measured hypertension at baseline. Of those diagnosed with hypertension, only 46.97% in 2013 had their blood pressure within the normal range in 2013, and this slightly improved to 47.80% in 2015. Both receiving a hypertension diagnosis (β = 0.41, 95% CI: 0.37–0.43) and having a low-SLE (β = 0.06, 95% CI: 0.03–0.09) were associated with healthier behavior. Interestingly, individuals with measured hypertension exhibited the highest SLE but the lowest health behavior scores.DiscussionAlthough individuals diagnosed with hypertension are able to recognize the dangers of the condition and take proactive steps to improve their health, high blood pressure remains uncontrolled in almost half of them. Those with measured hypertension often lack awareness of hypertension and unhealthier behaviors. Therefore, there is a critical need to enhance hypertension awareness and promote healthier behaviors among both diagnosed individuals with uncontrolled blood pressure and those unaware of their hypertension.